Identification of Personal Value and Its Relation to Positive Psychology and Happiness in a Lifestyle Group Case Study : Celebrity Fitness Member - Kumalasari, Diah (Journal of Business and Management, 2012)
This study investigates personal value, positive psychology and its relationship to happiness in a lifestyle group. Questionnaires were spread to members of Celebrity Fitness gym as a lifestyle group. There will be three different variables; personal value, positive psychology, and happiness. Kahleâ€™s List of Values is used to determine the value of the respondent. Happiness satisfaction is determined with life scale method by Ed Dienner and optimism. Positive psychology is calculated using PERMA framework, but this study only uses three of five factors that are Life of Pleasure, Life of Engagement, and Life of Meaning. These three variables are then made into four possible models of relationship, processed using Structural Equation Modeling with AMOS application. The outcome of this research is the difference of personal value and happiness level between members of Celebrity Fitness (lifestyle group) and non-members also the best equation model for the relationship of value, positive psychology and happiness. Keywords : Kahleâ€™s List of Value, Positive Psychology, PERMA, Satisfaction with Life Scale, Structural Equation Model (SEM) cï¿½Tmï¿½tï¿½ ï¿½ï¿½~ man","serif";mso-fareast-font-family:Helvetica'>Keywords : yield management, hotel industry, operating efficiency, demand plottingÂ